Faktor yang mempengaruhi Leverage sub sektor Pharmaceuticals di BEI - Hendra Hendra; Karlina Sopendi (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study was conducted with the aim of knowing whether there are effect of firm size, asset structure, liquidity, growth opportunities, profitability, and firm age on leverage. The population used in this study is the Pharmaceuticals Sub Sector on the Indonesia Stock Exchange from 2011 to 2020. Based on the purposive sampling method, 8 companies were sampled in the study. The data analysis method used is descriptive statistics and regression panel with a FEM model to testing all hypothesis. The conclusion that can be drawn from this research is that there is an effect of firm size, asset structure, and liquidity on leverage. Firm size and liquidity negatively effect to leverage because a mature company usually don’t need more debt to financing their activities. Asset structure have a positive effect to leverage because more asset means more collateral so company easy to get a loan. Meanwhile, growth opportunities, profitability, and company age have no effect on leverage.